Advances in Soft Tissue Tumors - Arnouk, Hilal (IntechOpen, 2022)
This book aims to foster collaboration between world-class bench scientists and clinicians in the fields of oncology, surgery, and pathology as they come together to highlight the complexity and diversity of soft tissue tumors as well as recent advances in their diagnosis and clinical management.